(untitled) (Research, Society and Development, 2020)
The purpose of this article is to present results of a research in which the results of four serological tests were compared for the diagnosis of swine brucellosis in pigs from Brazilian herds in which the outbreak occurred in relation to other brucellosis-free. Rose Bengal (RBT), complement fixation (CFT), agglutination plus 2-mercaptoethanol test (TAT+ME), and commercial fluorescence polarization assay (FPA) were used to test 333 sera (271 sows and 62 finishing pigs) from a Brucella suis infected swine herd and 1,100 swine sera from brucellosis free pigs taken at a slaughterhouse. Considering infected all the 271 sows from the outbreak, and interpreting results of the FPA according to the manufacturer directions, sensitivities observed were 95.94% for FPA, 94.83% for RBT, 93.73% for CFT, and 92.25% for TAT+ME. Considering infected all the pigs from the infected herd with a positive result in at least one test, sensitivities observed were 98.92% for RBT, 97.13% for CFT, 96.06% for FPA, and 94.98% for TAT+ME. Specificities of the tests were CFT and TAT+ME, 100%; FPA, 99.55%; and RBT 99.27%. Results indicated a good performance of all the tests, and the agreement among them was almost perfect.